2004
DOI: 10.1074/jbc.m401067200
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Hepatitis C Virus NS5B in the Subgenomic Replicon Cell Culture

Abstract: The hepatitis C virus (HCV) NS5B is an RNA-dependent RNA polymerase (RdRP), a central catalytic enzyme of HCV RNA replication. We previously identified five novel residues of NS5B in a JK-1 isolate indispensable for RdRP activity in vitro (Qin, W., Yamashita, T., Shirota, Y., Lin, Y., Wei, W., and Murakami, S. (2001) Hepatology 33, 728 -737). We addressed the role of these residues in HCV RNA replication using a HCV replicon system derived from an M1LE isolate (Kishine, H., Sugiyama, K., Hijikata, M., Kato, N.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 54 publications
(46 reference statements)
0
9
2
Order By: Relevance
“…This would help to explain how mutations in the ⌬1 loop, such as m26-30, and even the PV mutants were either incapable of or showed only a linear increase in de novo initiation activity with increasing enzyme concentrations. The residues in HCV NS5B identified to be critical for de novo initiation activity in this study, such as E18, L26-L30, and P495/ V499, have all been documented to be needed for HCV replication in cells, underlying their biological significance (8,10,32). The interdomain interactions may also be needed for productive RNA binding when longer RNA templates are used.…”
Section: Discussionmentioning
confidence: 91%
“…This would help to explain how mutations in the ⌬1 loop, such as m26-30, and even the PV mutants were either incapable of or showed only a linear increase in de novo initiation activity with increasing enzyme concentrations. The residues in HCV NS5B identified to be critical for de novo initiation activity in this study, such as E18, L26-L30, and P495/ V499, have all been documented to be needed for HCV replication in cells, underlying their biological significance (8,10,32). The interdomain interactions may also be needed for productive RNA binding when longer RNA templates are used.…”
Section: Discussionmentioning
confidence: 91%
“…We found that another mutant replicon, MA/K211A, reduced the number of G418-resistant colonies compared with the wild type and the other mutants. Because K211A of NS5Bt is close to the pocket of catalytic activity and did not affect binding to nucleolin, K211 may contribute to the structural integrity of the pocket or the heat-stable property of RdRp as reported previously (36).…”
Section: Discussionmentioning
confidence: 88%
“…1A). The wild-type replicon was represented by MA, in which S232 of NS5A was altered to I, because this mutant replicon can efficiently replicate in Huh7 cells (36,56). In the replicon MA/cm211, each of the amino acids at positions 208 to 214 of NS5B was changed to alanine, whereas in the replicons MA/ W208A, K209A, S210A, K211A, K212A, C213A, and P214A, each individual amino acid residue was changed to alanine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations